2022
DOI: 10.3390/ijerph192013562
|View full text |Cite
|
Sign up to set email alerts
|

Capital Formation, Green Innovation, Renewable Energy Consumption and Environmental Quality: Do Environmental Regulations Matter?

Abstract: The world economy continues to witness a steady rise in carbon emissions, which makes it challenging to fulfill the terms of the Paris agreement on reducing greenhouse gas emissions. In this context, countries worldwide enact environmental regulations to curtail environmental pollution to promote sustainable development. However, the importance of environmental regulations has not been fully validated in the previous literature. In addition, the concurrent roles of capital formation, green innovation, and rene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…This concept is also supported by the study's findings. These findings are consistent with those of the study by Meng et al (2022).…”
Section: Empirical Findings and Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This concept is also supported by the study's findings. These findings are consistent with those of the study by Meng et al (2022).…”
Section: Empirical Findings and Discussionsupporting
confidence: 94%
“…coal, oil and gas). Achieving sustainable development goals in this approach can be greatly aided by CAP and environmental regulation (Meng et al, 2022). It can be said that there is a direct correlation between capital and GRG because investments in low‐carbon and other environmentally friendly projects demand more technology and capital‐intensive growth.…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
“…In contrast, appropriate environmental regulation incentivizes technological innovation (Wu et al, 2020). Most studies focus on regulations and GI, within a country, such as China, or between economies (Meng et al, 2022; Nazir et al, 2023; Tang et al, 2020; Xu et al, 2022; Zhou et al, 2021). Command‐based environmental regulations may undermine firms' competitiveness in the long run, whereas market‐based policies have lasting incentive effects through price signals and voluntary instruments that guide production model transformation via enhancing environmental awareness (Xu & Cui, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, appropriate environmental regulation incentivizes technological innovation (Wu et al, 2020). Most studies focus on regulations and GI, within a country, such as China, or between economies (Meng et al, 2022;Nazir et al, 2023;Tang et al, 2020;Xu et al, 2022;Zhou et al, 2021) Cui, 2020). Market-based policies have been promoted in recent years.…”
Section: Environmental Regulation and Gimentioning
confidence: 99%
“…Kazen et al (2021) examined the inverted U-shaped impact of GFC on carbon emissions in G20 countries, whereas Hata et al (2022) disagreed and concluded that fixed capital formation, in terms of machinery and infrastructure, always increases pollution. Xueying et al (2022) and Quanliang et al (2023) concluded that the management of fixed-capital formation is essential to avoid pollution. In this study, environmental hazards stand as the dependent variable and are limited to greenhouse gas emissions, while forests, population, capital formation, and energy consumption serve as explanatory variables.…”
Section: Introductionmentioning
confidence: 99%